Understanding Motives of Indigenous Cattle Farmers Joining Farmers Group in Brebes Regency, Indonesia - Mochamad Sugiarto; Yusmi Nur Wakhidati; Oentoeng Edy Djatmiko; Syarifuddin Nur; Dyah Gandasari (ANIMAL PRODUCTION, 2021)
The development of Jawa Brebes (Jabres) cattle as indigenous cattle in Brebes Regency, Indonesia, is carried out using a farmer group approach. Cattle farmers join farmer groups with various motives and purposes. Understanding the motives of indigenous cattle farmers joining farmers group in Brebes Regency, Indonesia, this study aimed to identify the motives of Jabres cattle farmers to join the group and analyze the influencing factors of different motives to join farmers group. The study used a survey method to 119 Jabres cattle farmers in Brebes Regency. Respondents were selected using multistage sampling. Data were analyzed using descriptive statistics to depict the cattle farmers' characteristics and identify their motives to join the farmers' group. Discriminant analysis identified the influencing factors of Jabres cattle farmers' different reasons for joining the Jabres cattle farmers group. The majority of the Jabres cattle farmers in Brebes Regency (75.6 percent) entered the farmers' group due to social motive and expectancy to feel secure in social interactions with other farmers. Farmer's education is an essential factor that causes differences in cattle farmers' motives in joining farmer groups (P <0.05). Cattle farmers with higher education join the farmers’ group to gain additional knowledge and realize beef cattle business goals (profitability and marketing).